Parents' intentions toward including their children with visual impairments in physical activities. Issue 5 (27th February 2020) - Columna, Luis; Streete, Denzil A.; Rocco-Dillon, Suzanna; Hodge, Samuel R.; Prieto, Laura; Myers, Beth; Barreira, Tiago V.; Heffernan, Kevin S.
Abstract: Purpose: Physical activity participation is essential for the healthy development of basic locomotor skills and for the overall wellbeing of children. Unfortunately, for children with visual impairments the opportunities to engage in physical activity are limited compared with their peers without disabilities. The purpose of this study was to determine and analyze the intentions of parents to include their children with visual impairments, as well as their entire family in physical activities after participating in a physical activity intervention. Methods: This descriptive-qualitative study was situated in the theory of planned behavior. On completion of a series of workshops, 10 parents took part in individual semi-structured interviews that were subsequently transcribed and analyzed using a thematic line-by-line analysis. Results: Through the data analysis three major themes emerged: (a) increased confidence, (b) influence on future intentions, and (c) conditional intentions. Conclusions: Results revealed that the physical activity intervention provided parents with an opportunity to engage their child in physical activities and to gain a deeper understanding of their child's disability. Consequently, the intervention enhanced parent's perceived teaching abilities and skills regarding physical activity. Implications for rehabilitation: Results of this study demonstrated that a physical activity intervention have the potential to enhance intentions to engage in physical activity among children with visual impairments and their parents. As a result of this study, parents acquired the skills necessary to confidently engage their children in physical activity. The current physical activity intervention provided parents with an opportunity to engage their child in physical activities and to gain a deeper understanding of their child's disability. Physical activity interventions targeting children with visual impairments and their parents should consider the inclusion of oral presentations combined with written supplements or written manuals, and physical activity equipment.